Student Responsible Learning: Getting Students to Read Online Discussions. Issue 2 (3rd April 2017) - Stearns, S. A.
ABSTRACT: Designing courses for optimal level student learning is dependent upon student participation. This study examined one way to encourage further student participation in online discussions. Of specific importance was how to encourage students to read their student-colleagues' online discussion responses: not just a minimum number of responses but the majority of the responses. Results illustrate that the method utilized, Thematic Analysis, is effective in increasing reading rates among students. But possibly even more interesting are the students' reports that the use of this learning tool encouraged them to think critically and that their learning occurred primarily through many of the tenets of social constructivist theory. Furthermore, students reported enjoying this process of learning.